Spectrophotometric analysis of surface free energies of polymer surfaces - Odeh, Calistus Princewill; N.Ezenwa, O.; Chinweze, Arinze Everest; Okafor, Anthony Amaechi (International Journal of Engineering and Technology, 2024)
This work is focused on the use of a spectrophotometer to determine the surface free energies of polymers. To study the molecular system interaction, there is a need for a simpler method to calculate free energy. The free energy determines the phase interaction of polymer film at different concentrations. One of the simpler methods is the use of a spectrophotometer. The methodology involved taking four polymer samples and dissolving each into different concentrations for absorbance measurement using an ultraviolet spectrophotometer. From the absorbance data, various variables (e.g., dielectric constant, etc.) were derived. This variable (dielectric constant) was also used to determine the haymaker constant of each concentration of each polymer. The surface free energies are determined from the values of the Hamaker constant. The peak values of surface free energies for Polyvinyl alcohol (PVA), Polyethylene glycol (PEG) and Polyacrylamide (PAM) were also obtained from spectrophotometer results and found to be the same, 57.51mJ/m^2. Contact angle measurements on concentration were also obtained. It was found that the contact angle measured on PVA and PEG at different concentrations tends to decrease with an increase in concentration. The results, therefore, show that PVA and PEG surfaces tend to be hydrophilic as concentration increases while PAM and Polyvinyl acetate (PVAC indicate hydrophobic. Surface free energies obtained from the spectrophotometric result and contact angle show little significant difference of about 6.9% and they followed the trend when related with other surface properties.